Innovative Design of Intelligent Detection Equipment for Growth Information of Facilityhorticultural Crops - Ruan, Yu Qiang; Xiao Dong Zhang; Hanping Mao; Hong Yan Gao; Xin Zhang; QinLin li (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Intelligent equipment technology for facility horticulture is an urgent need for the development of modern facility agriculture.The intelligent monitoring equipment for greenhouse crop growth information can comprehensively monitor the nutrition, growth and environmental information of crops, and provide a scientific basis for the optimal regulation and control of water, fertilizer and environment in the greenhouse. It is a key equipment for the intelligentization of facility horticulture. This research aims at different growth stages In accordance with the testing needs of different plant-shaped crops and the operational needs of the unstructured environment in the greenhouse, we developed wheeled and tracked crop growth and environmental information monitoring systems that can autonomously cruise in the greenhouse;at the same time, in order to meet the detection needs of large-plant crops, a cantilever type crop information monitoring system has also been developed. This system suspends the multi-sensor detection system through the gimbal and installs it on the orbit track laid on the greenhouse truss. Because the detection position is high, it is realized the cruise monitor of greenhouse plants such as cucumber and tomato. In order to achieve comprehensive detection of crop growth information, a multi-sensor detection system for horticultural crop information has been developed. It uses visible-near-infrared binocular multi-spectral cameras, infrared detection sensors, laser ranging sensors, ambient temperature and humidity and light sensors. through the multiple sensor information fusion, implements the facilities horticulture crops nutrition, growth and the comprehensive monitoring of environmental information. Good application effect has been achieved.